The philosophy of Arabic grammar: its impact on world history and human civilization (including Malay civilization) - Yaacob, Solehah @ Nik Najah Fadilah (Self-published, 2025)
God exists, and indeed, God exists in the minds of those who critically comprehend the inimitability of the Quran. This book delivers the power of philosophy of the Arabic grammar as a tool in demonstrating the refutation of the most pronounced and frequent arguments postulated by atheism, which are inconsistent with God’s revelation. It also looks into the debate on the role of religious belief in education from the Islamic viewpoint. The rationale of delving into this debate is the silent but growing rejection of the role of religion in educating future generations among Muslims who have taken the position that religious education has failed and has only exacerbated the lack of economic, social, and political progress in the Muslim world. Islamic intellectual revivalism, especially cloaked in the Arabic-centric world rather than Western-oriented, is under constant attack within and outside the realm of humanizing education. For Muslims, the existence of God or a Single Lone Creator is beyond doubt or debate solely based on the inimitability of the Quran. This book takes up the argument that Arabic grammar refutes the idea of non-existent divinity promulgated by atheism since the Holy Book has been consistent linguistically and philosophically in demonstrating that God is one and permanent. Thus, the primary objective of this book is to facilitate the understanding of the connection between philosophy and Arabic grammar as a means to understand man’s existence and his place in the cosmic universe. In other words, why was man created? And to what purpose does his existence serve? It could not be for naught, merely to exist and inevitably decompose into dust. Therefore, this book argues that Arabic grammar with its reliance on deep contemplation is ultimately connected to issues of metaphysics. The idea of authoring a book on `Philosophy of Arabic Grammar: Its Impact on the World History and Human Civilization` was requested by Prof. Dr. Shukran Abdul Rahman, Former Dean of my Kulliyyah, for my inaugural professor presentation. To honor his suggestion, I scrutinized the data I had, including the necessary topics to be added. This resulted in the unavoidable repetition of certain materials when the methodologies used by the authors of those materials were rigorously scrutinized. Along with that, the objective of the writing of this book is to accelerate the understanding of the connection between philosophy and Arabic grammar among those looking for a quick search on the subject. Regardless of the semantic element's role in quantifying this knowledge, which is composed of multiple processes, it must still be thoroughly deliberated. Our view is that Arabic linguistic and its semantics constitute a lingua revolution that matches the cognitive domain of the human mind. By using the term lingua revolution, we mean a change that occurs at the cognitive-psychological level of the human mind and the most fundamental level of human consciousness, his soul. The difference is profound. It involves structural change: an internalized change manifested by the subsequent emergence of a new personal or communal identity. The book consists of six chapters, whereas each chapter develops the narrative of the objective and theme of the book itself. Chapter 1: Philosophy of Arabic Grammar in Interpreting semantic changes The philosophy of Arabic grammar is a tool for delving into a profound structure concept linguistically. It is also a tool to explain semantic changes resulting from phonetic changes in word endings especially concerning vowels structurally. It further looks into the dynamics which bring about such changes in phonetics and evaluates the significance of the altered meanings from the viewpoint of semantics. Thus, the interpretation of semantics needs to be modified by using the theory of NaÐm. However, to avoid errors in applying such a system, it is necessary to express the same meaning in different ways, defined as the art of eloquence.